Standards - Norasage Pattanadech; Rainer Haller; Stefan Kornhuber; Michael Muhr (My University, 2023)
Partial discharge (PD) tests according to the standards are to prove the quality and condition of insulation systems applied for high-voltage (HV) apparatus and their components. The test procedures for quality assurance after manufacturing and repair, as well as the test voltages and their limits of tolerated PD magnitude, are deduced from long-time experience. The horizontal standard that applies to all areas is IEC 60270 "High-Voltage Test Techniques – Partial Discharge Measurement". But there are also associated standards for the various apparatus that include regulations for PD testing. Beyond the standards, there are many important documents and publications regarding PDs. Especially, CIGRE has published a lot of technical brochures referring PD behavior in HV apparatus. PD books are those that deal specifically with PD only.
Keywords: High voltage insulation and dielectric phenomena; Power Transformer Diagnostics and Insulation; Thermal Analysis in Power Transmission